Exhibiting Italian art in the United States from Futurism to Arte povera : "like a giant screen" - Bedarida, Raffaele, 1979- (New York : Routledge, Taylor & Francis Group, 2022)
"This volume explores how Italian institutions, dealers, critics, and artists constructed a modern national identity for Italy by exporting -literally and figuratively - contemporary art to the United States in key moments between 1929 and 1969. From artist Fortunato Depero opening his Futurist House in New York City to critic Germano Celant launching Arte Povera in the US, Raffaele Bedarida examines the thick web of individuals and cultural environments beyond the two more canonical movements that shaped this project. By interrogating standard narratives of Italian Fascist propaganda on one hand and American Cold War imperialism on the other, this book establishes a more nuanced transnational approach. The central thesis is that, beyond the immediate aims of political propaganda and conquering a new market for Italian art, these art exhibitions, publications, and the critical discourse aimed at American audiences all reflected back on their makers: they forced and helped Italians define their own modernity in relation to the world's new dominant cultural and economic power. The book will be of interest to scholars working in art history, social history, exhibition history, and Italian studies"--
(Prelude): "I Will Smash The Alps of the Atlantic:" Futurist Depero and Italian Americanism -- Exporting Fascist Culture/Importing American Modernity -- MoMA and the Post-War Rehabilitation of Italy -- Tu Vuo Fa l'Americano: Catherine Viviano, Irene Brin, and Italian Art's Conquest of Hollywood -- Transatlantic Arte Povera: The Trojan Horse of Germano Celant.
Based on the author's thesis (doctoral)--City University of New York, 2016, under the title: Export/import : the promotion of contemporary Italian art in the United States, 1935-1969.
Keywords: Art, Italian -- 20th century -- Exhibitions; Art publicity -- United States -- History -- 20th century; Exhibitions -- United States -- History -- 20th century; Italy -- Relations -- United States; United States -- Relations -- Italy